2023
DOI: 10.3390/ani13050920
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation Quality, In Vitro Digestibility, and Aerobic Stability of Ensiling Spent Mushroom Substrate with Microbial Additives

Abstract: This experiment investigated the effects of lactic acid bacteria and cellulase on the fermentation quality, in vitro digestibility, and aerobic stability of Flammulina velutipes spent mushroom substrate silage (F-silage) and Pleurotus eryngii spent mushroom substrate silage (P-silage). Silage treatments included groups without any additives (control), with lactic acid bacteria (L), with cellulase (E), and with lactic acid bacteria and cellulase (M). Data analysis was performed using independent sample t-test a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…In Pennisetum sinese silage, cellulase reduced the crystallinity of lignocellulose and improved its conversion, indicating that it was a very useful silage pretreatment method [44]. Under 60% MC conditions, the NDF, ADF, and ADL contents in the L group were lower than those in the control group, which was consistent with the findings of Yi et al [31]. These authors also found that inoculation of lactic acid bacteria in Pleurotus eryngii silage reduced the NDF, ADF, and ADL contents in P. eryngii silage.…”
Section: Effect Of Moisture Content and Additives On Chemical Composi...supporting
confidence: 89%
See 1 more Smart Citation
“…In Pennisetum sinese silage, cellulase reduced the crystallinity of lignocellulose and improved its conversion, indicating that it was a very useful silage pretreatment method [44]. Under 60% MC conditions, the NDF, ADF, and ADL contents in the L group were lower than those in the control group, which was consistent with the findings of Yi et al [31]. These authors also found that inoculation of lactic acid bacteria in Pleurotus eryngii silage reduced the NDF, ADF, and ADL contents in P. eryngii silage.…”
Section: Effect Of Moisture Content and Additives On Chemical Composi...supporting
confidence: 89%
“…Marbun et al [30] showed that the addition of L. plantarum to the silage process reduced the AN/TN and fungal counts in maize silage effectively improved the fermentation quality of maize silage. Yi et al [31] inoculated lactic acid bacteria during the silage of spent mushroom substrate, which improved the fermentation quality. This was explained by the fact that the addition of homofermentative lactic acid bacteria preparations can promote the early entry of silage into lactic acid fermentation, change the situation of insufficient lactic acid bacteria in the early stage of fermentation, and produce large amounts of LA to reduce the pH and AN/TN of silage, thus inhibiting the growth and reproduction of yeasts and molds and reducing nutrient losses [32].…”
Section: Effect Of Moisture Content and Additives On The Fermentation...mentioning
confidence: 99%
“…Furthermore, the content of AA during silage fermentation should also be emphasized, and AA is often used as a poor silage fermentation inhibitor. Studies have shown that silage containing high concentrations of AA has lower yeast and mold populations and higher aerobic stability, AA can effectively reduce the pH value of silage, and its inhibitory effect on yeast is even greater than LA (Danner et al, 2003 ; Liu et al, 2020 ; Selwet, 2020 ; Yi et al, 2023 ), which is obvious in its inhibitory effect. In this experiment, although the difference in AA content was not significant in all groups after 14 days of ensiling ( P > 0.05), the AA content of group L was extremely significantly higher than other groups after 56 days of ensiling ( P < 0.01), while the yeast count of group L and LM was also extremely significantly lower than in group CK and M ( P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Mold was observed in the CK and LP groups on day 1 of ensiling, but it disappeared as the duration of ensiling and salt concentration increased. This may be attributed to the metabolites produced by LAB, which inhibit the growth of harmful bacteria such as Clostridium botulinum and mold ( Qixuan et al., 2021 ). LAB and Escherichia coli were the most abundant microbial types during ensiling.…”
Section: Discussionmentioning
confidence: 99%